Investigating the Quality of Caring Behaviors of Nurses and Patient Satisfaction in Shahid Beheshti Hospital of Yasuj - Soheila Zabolypour; Kourosh Dastan; Saeed Ghorbani; Amir Anbari; Sepideh Mohammadi (Golestan University of Medical Sciences, 2016)
Background: Caring is the core of Nursing and holistic high-quality care is considered as one of the main concerns of nursing managers. Evaluation by main care recipients and assessment of their satisfaction with different levels of care is a way to determine and improve the quality of nursing care. The aim of this study was to determine the relationship between the quality of nurses' caring behaviors with patient satisfaction in four areas of nursing knowledge and skills, patient education, communication and nursing ethics. Methods: This descriptive study was performed on 150 patients hospitalized in the Shahid Beheshti Hospital of Yasuj, in 2013. Subjects were selected by convenience sampling and from the departments of general surgery, neurosurgery, infectious diseases, neurology and burn center. Data were collected and analyzed using quality of caring behaviors and patient satisfaction questionnaires. Results: The quality of caring behaviors was reported as moderate by the patients. Subscale of quality of caring behaviors was reported as good in area of nursing knowledge and skills, and as moderate in areas of patient communication and nursing ethics. The mean score of satisfaction was relatively favorable. Satisfaction regarding the subscale of nursing knowledge and skills was at a favorable level and patient education, communication and nursing ethics were reported as relatively favorable. Conclusion: Considering the moderate quality of nursing care, patient satisfaction level and level of the subscales, nursing managers and officials at faculty of nursing are expected to pay more attention to the aspects of patient education, communication and nursing ethics in addition to nursing knowledge and skills.